The justice of Gideon - Gates, Eleanor, 1875-1951; Dunn, Harvey, 1884-1952 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Justice of Gideon" by Eleanor Gates is a novel written in the early 20th century. The book centers around Gideon Carr, a Justice of the Peace in the small town of Manzanita, California, as he navigates both legal matters and personal relationships. Key themes include justice, ambition, and the complexities of human interactions, particularly focusing on the characters Gideon, Alicia, and Homer. The opening of the narrative sets a vivid scene in Gideon's courtroom, emphasizing both the physical space and the weight of his responsibilities. He is preparing for a day of trials when Alicia, a girl he seems to have affection for, enters with concerns about Homer, a young man whom Gideon has helped raise. As Alicia reveals gossip about Homer gambling and potentially getting into trouble, the Judge's protective instincts come into play. This opening not only establishes the main characters and their relationships but also hints at impending conflicts that will test Gideon's sense of justice and personal connections as the story unfolds. (This is an automatically generated summary.)
The justice of Gideon -- Doc -- The boomerang -- Buenas noches -- Little watcher -- Missy and I -- The Genevieve epidemic -- Agatha's escort -- Yellow man and a white -- Yee Wing, powder-man -- The search for the spring -- The silver bell of Los Morales -- The revenge of Manuelita.
Release date is 2024-04-02
D A Alexander, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Short stories, American; California -- Social life and customs -- Fiction; American fiction